Strain Partitioning and Interseismic Fault Behavior Along the Caribbean‐South American Transform Plate Boundary. Issue 8 (16th August 2021) - Higgins, M.; La Femina, P. C.; Weber, J. C.; Geirsson, H.; Ryan, G. A.; Wauthier, C.
Abstract: We combine Global Positioning System and Interferometric Synthetic Aperture Radar (InSAR) data to characterize the interseismic behavior (i.e., locked or creeping), and strain partitioning for the faults along the Caribbean‐South American transform plate boundary. Interseismic strain is distributed mainly on three faults, the San Sebastian, El Pilar, and Central Range faults, but partitioning occurs across multiple faults in the west (San Sebastian and La Victoria faults) and east (Sub‐Tobago Terrane, Central Range, and South Coast faults). In northern Venezuela, slip is partitioned on the San Sebastian (16.4 ± 1.7 mm/yr) and La Victoria (4.3 ± 0.9 mm/yr) faults. In north‐eastern Venezuela, the El Pilar fault accommodates slip at a rate of 18.6 ± 1.8 mm/yr. In Trinidad and Tobago, slip is partitioned between the Sub‐Tobago Terrane (3.0 ± 0.1 mm/yr), Central Range (14.5 ± 2.0 mm/yr), and South Coast (3.0 ± 0.1 mm/yr) faults. The La Victoria, San Sebastian, the western El Pilar segment, and Sub‐Tobago Terrane faults are locked to depths of 16.2 ± 4.0 km, 7.7 ± 5.2 km, 6.7 ± 2.8 km, and 8.0 ± 0.2 km, respectively. The eastern segment of the El Pilar, the Central Range, and the South Coast faults all creep. Our new InSAR results indicate that the entire Central Range Fault is creeping. The locked western segment of this transform plate boundary is capable of producing a Mw 8 earthquake, which is a significant finding regarding seismic hazard and risk. Key Points: CA‐SA relative plate motion is partitioned along the transform boundary on multiple fault segments Plate boundary faults are locked west of 64°W, while faults to the east are creeping, except the Sub‐Tobago Terrane fault The western segment of the plate boundary could produce a Mw 8 earthquake